Identification of genes associated with persistence in Mycobacterium smegmatis - Joshi, Hemant; Kandari, Divya; Maitra, Subhrangsu Sundar; Bhatnagar, Rakesh; Banerjee, Nirupama (Frontiers in Microbiology, 2024)
The prevalence of bacterial persisters is related to their phenotypic diversity and is responsible for the relapse of chronic infections. Tolerance to antibiotic therapy is the hallmark of bacterial persistence. In this study, we have screened a transposon library of Mycobacterium smegmatis mc 2 155 strain using antibiotic tolerance, survival in mouse macrophages, and biofilm-forming ability of the mutants. Out of 10 thousand clones screened, we selected ten mutants defective in all the three phenotypes. Six mutants showed significantly lower persister abundance under different stress conditions. Insertions in three genes belonging to the pathways of oxidative phosphorylation msmeg_3233 (cydA), biotin metabolism msmeg_3194 (bioB), and oxidative metabolism msmeg_0719, a flavoprotein monooxygenase, significantly reduced the number of live cells, suggesting their role in pathways promoting long-term survival. Another group that displayed a moderate reduction in CFU included a glycosyltransferase, msmeg_0392, a hydrogenase subunit, msmeg_2263 (hybC), and a DNA binding protein, msmeg_2211. The study has revealed potential candidates likely to facilitate the long-term survival of M. smegmatis. The findings offer new targets to develop antibiotics against persisters. Further, investigating the corresponding genes in M. tuberculosis may provide valuable leads in improving the treatment of chronic and persistent tuberculosis infections.